Unit six - Water use in agriculture: small-scale irrigation and rainwater harvesting. [Training/Course material] - David, S.; Fraiture, Charlotte de; Atapattu, Sithara S.; Smith, L. (2009)
This unit provides an introduction to some of the key elements of the role and importance of water resources in smallholder agriculture. The first section introduces the basic concepts at the farm level by looking at farm productivity and the role of men and women which is essential in understanding the linkages between the livelihoods of the people and poverty alleviation. Section 2 explores water management concepts and issues in smallholder rainfed agriculture, including a range of practices that show promise in best supporting livelihoods and utilising available resources. Rainfed agriculture is critically important, as most rural poor depend solely on rain as their water source and there are many means to upgrade the performance of these systems. Some of these ways require a small amount of irrigation. Section 3 leads into small-scale irrigation. This section summarises and provides the differences between individual versus community based systems including management styles and key considerations in the design and management of these systems. In Section 4, the multiple uses of water, the use of water for household and industrial uses as well as farming, at the farm and household level are presented. Multiple uses of water provide an ideal way of obtaining more benefits per unit of water. Unit aims: To introduce and explain the linkages between small-scale water resource management in agriculture, food security, livelihoods and poverty; To identify the important roles of both men and women in small-scale farming and water management systems; To introduce key concepts of rainfed agriculture in the context of the 'blue-green water' continuum and identify the strengths of and constraints to different methods of rainwater water management; To introduce the concept of irrigation in small-scale agriculture and to look at the two main ways of managing it: individual compared to community based management; To introduce the concept of multiple uses for water by rural households and to describe some of the key uses in detail; To provide a basic understanding of multiple uses of water and the approaches available to manage them; To assess the importance of fisheries and livestock production as competitors for water with irrigated crop production.